Timing of contraceptive initiation and association with future sexual and reproductive outcomes - True, Kimberley (Oxford University Press, 2014)
STUDY QUESTION: Who initiates contraception before, at the time or after first sexual intercourse and how does timing of initiation affect future sexual and reproductive health (SRH) outcomes? SUMMARY ANSWER: Earlier initiation was associated with current utilization of more effective contraception, but had no impact on future unintended pregnancy, abortion or sexually transmitted infection rates, while later initiation was linked to higher rates of unintended pregnancies and abortions. WHAT IS KNOWN ALREADY: Contraceptive behaviour at first intercourse is associated with later SRH outcomes. STUDY DESIGN, SIZE, DURATION: Data were drawn from the FECOND study, the last national SRH study in France, conducted in 2010–2011 by phone among 8645 individuals aged 15–49 years. PARTICIPANTS/MATERIALS, SETTING, METHODS: Analysis was performed among 1552 women under the age of 30 years who were sexually experienced and had used contraception at some point. We used logistic regression models to identify factors associated with timing of contraception initiation relative to first intercourse (earlier, at the time and later) and its predictive value on future sexual and reproductive outcomes. MAIN RESULTS AND THE ROLE OF CHANCE: Timing of contraceptive initiation across all three categories (earlier, at the time and later initiators) was dependent on women's age at the time of the survey, country of birth, education level, ease of discussing sex with mother and age of first sex. Using at the time initiators as a reference, later initiators had higher odds of unintended pregnancy [odds ratio (OR) = 1.8] and abortion (OR = 1.9), while earlier initiators were more likely to be using more effective contraception at the time of the survey (OR = 1.8). LIMITATIONS, REASONS FOR CAUTION: The exclusion of sexually inexperienced women, a quarter of which had ever used the pill, may have reduced the scope of our analysis on the relevance of contraceptive initiation for non-contraceptive benefits. WIDER IMPLICATIONS OF THE FINDINGS: The promotion of early initiation of contraception may contribute to long-term use of more effective methods of contraception. STUDY FUNDING/COMPETING INTEREST(S): The FECOND study was supported by a grant from the French Ministry of Health, a grant from the French National Agency of Research (#ANR-08-BLAN-0286-01; PIs N. Bajos, C Moreau) and funding from the National Institute of Health and Medical Research (INSERM) and the National Institute for Demographic Research (INED). None of the authors have a conflict of interest.